2022
DOI: 10.3389/fimmu.2022.812126
|View full text |Cite
|
Sign up to set email alerts
|

Reduced T Cell and Antibody Responses to Inactivated Coronavirus Vaccine Among Individuals Above 55 Years Old

Abstract: CoronaVac is an inactivated SARS-CoV-2 vaccine that has been rolled out in several low and middle-income countries including Brazil, where it was the mainstay of the first wave of immunization of healthcare workers and the elderly population. We aimed to assess the T cell and antibody responses of vaccinated individuals as compared to convalescent patients. We detected IgG against SARS-CoV-2 antigens, neutralizing antibodies against the reference Wuhan SARS-CoV-2 strain and used SARS-CoV-2 peptides to detect I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…Supplementary analysis based on vaccine type (details in the Supplementary Figure 6) revealed differences in antibody titers and positivity rates between the two vaccines (both the antibody titer and seropositivity rate induced by Corona Vac were higher than those induced by BBIBP-CorV), indicating that vaccine type is one of the factors influencing antibody response, consistent with the multivariate linear regression analysis results of vaccine type for antibody response and previous studies (30). Meanwhile, we also found that age was not associated with immune response in MS patients, but previous studies showed that age ≥70 was associated with a poorer antibody response in chronic obstructive pulmonary disease patients (COPD) (31) and the immune response was lower for persons over 55 years of age (32). These findings could be attributed to the small sample size, or they could indicate that the immune response would not have been significantly different in this specific population.…”
Section: Discussioncontrasting
confidence: 49%
“…Supplementary analysis based on vaccine type (details in the Supplementary Figure 6) revealed differences in antibody titers and positivity rates between the two vaccines (both the antibody titer and seropositivity rate induced by Corona Vac were higher than those induced by BBIBP-CorV), indicating that vaccine type is one of the factors influencing antibody response, consistent with the multivariate linear regression analysis results of vaccine type for antibody response and previous studies (30). Meanwhile, we also found that age was not associated with immune response in MS patients, but previous studies showed that age ≥70 was associated with a poorer antibody response in chronic obstructive pulmonary disease patients (COPD) (31) and the immune response was lower for persons over 55 years of age (32). These findings could be attributed to the small sample size, or they could indicate that the immune response would not have been significantly different in this specific population.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies reported deficient production of vaccine-induced antibody titers after CoronaVac application, especially among elderly and immunocompromised individuals. 12 15 Our results demonstrate that the ZnONRs/spike immunosensor can detect the anti-SARS-CoV-2 spike protein antibody in individuals vaccinated with CoronaVac. This point-of-care technology can specifically aid public health actions in assessing humoral immune response post-COVID-19 vaccination in the countries where this vaccine is applied.…”
Section: Resultsmentioning
confidence: 70%
“…A case-control study observed that the vaccine efficiency descended with increasing age among the elderly people (≥70 years) in Brazil(2021). Recently, a significant reduction in T-cell and antibody responses to inactivated coronavirus vaccination has been reported in people aged 55 years or older ( 58 ). With much attention that has been paid to the immune response of elderly people (≥60 years) after vaccination, the protection effectiveness of CoronaVac against SARS-CoV-2 in middle-aged people (50-59 years) deserves more attention.…”
Section: Discussionmentioning
confidence: 99%